Impact of Solid Waste Management Practices on Human Health in Siliguri Municipal Corporation (SMC), West Bengal, India: A Geographical Analysis (International Journal of Food and Nutritional Sciences, 2021)
This present study examines the relationship between solid waste management practices and public health outcomes in Siliguri Municipal Corporation (SMC), through a comprehensive analysis of secondary data from government reports, published research studies, and official health statistics. It investigates how inadequate waste management systems contribute to disease prevalence and environmental health challenges. The study reveals significant correlations between waste accumulation patterns and vector-borne and respiratory ailments in the study area. Findings indicate that areas with poor waste collection services experience higher incidence of waterborne and respiratory complications compared to well-serviced areas. The research emphasises the need for integrated waste management strategies that consider geographical constraints and population density variations across the municipal area.